Investigations on Specific Phytochemical Characteristics of Seed Oil and Defatted Seeds of Four Oil-Producing Plants Found in Cameroon - Tangka, Julius K.; Bongmo, Jaff Marilyn; Etengeneng, Agbor Esther (European Journal of Applied Sciences, 2024)
A study was conducted to find and create new possible sources of seed oils that might be extracted locally and utilised in Cameroon to produce biodiesel, while also valuing the defatted seeds as alternate sources of nutrients for consumption by humans and animals. Pretreatment procedures included washing and drying the seeds of Ricinodendron heudelotii (njangsa), Cucurbita maxima (pumpkin), Citrullus lanatus (watermelon), and the pulp of Raphia hookeri (raphia). A hydraulic press operating at 200 bars was then used to extract the oil from each sample. A proximate analysis was performed on both the defatted and intact seeds. While the proximate composition of the defatted cakes was examined, the extracted oils’ potential for use as biodiesel was examined. The four samples’ oil quality parameters were determined to be as follows: acid value (3.6 to 5.8 mgKOH/g), iodine value (19.0 to 39.0 gI2/100g), saponification value (56.1 to 280.6 mgKOH/g), and oil extracted (11.40% to 37.40%). All samples’ crude protein, crude ash, and crude carbohydrate contents increased after defatting, whereas their crude lipid and crude fibre contents decreased. The highest protein content was found in defatted pumpkin seeds (41.11% DM), whilst the lowest protein content was found in defatted raffia palm pulp (7.35% DM). The findings of the oil parameter analysis indicated that all four oils have the potential to be employed as low-cost alternatives as feedstock for the production of biodiesel. The defatted seeds’ results demonstrated that, with the exception of lipids, defatting concentrates macronutrients.